Cardiovascular morbidity and mortality is increased post‐liver transplantation even in recipients with no pre‐existing risk factors. (10th July 2019) - De Luca, Laura; Kalafateli, Maria; Bianchi, Simone; Alasaker, Norah; Buzzetti, Elena; Rodríguez‐Perálvarez, Manuel; Thorburn, Douglas; O'Beirne, James; Patch, David; Leandro, Gioacchino; Westbrook, Rachel; Tsochatzis, Emmanuel A.
Abstract: Background/aims: Post‐liver transplant (LT) metabolic syndrome (PTMS) and cardiovascular (CVS) mortality are becoming increasingly prevalent following sustained improvements in post‐LT survival. We investigated the prevalence and predictors of PTMS and CVS complications in a cohort of consecutive LT recipients. Methods: We reviewed prospectively collected data of patients (n = 928) who underwent LT (1995‐2013) and survived at least 1‐year post‐LT or died before that due to a major CVS complication. Results: Median follow‐up was 85 months (IQR = 106). The prevalence of PTMS was 22.4% and it developed de novo in 183 recipients (19.7%). A total of 187 (20.2%) patients developed at least one CVS event post‐LT within a median of 49 months (IQR = 85). Overall mortality rate was 22.6% (n = 210). Causes of death were CVS events (n = 45, 21.4%), malignancies (21%), liver‐related deaths (20%) and infections (6.7%). Independent predictors of major CVS events were: documented CVS disease pre‐LT (Hazard Ratio (HR) = 3.330; 95% CI = 1.620‐6.840), DM (HR = 1.120; 95% CI 1.030‐1.220), hypertension (HR = 1.140; 95% CI 1.030‐1.270), dyslipidaemia (HR = 1.140; 95% CI 1.050‐1.240) and creatinine levels at 1 year (HR = 1.010; 95% CI = 1.005‐1.013). Among LT recipients without pre‐LT CVS disease or MS components (n = 432), 85 recipients developed ≥1 CVS events (19.7%) with independent predictors being DM (HR = 1.150; 95% CI = 1.010‐1.320), creatinine levels at 1 year (HR = 1.020; 95% CI = 1.010‐1.030) and hypertension (HR = 1.190; 95% CI = 1.040‐1.360). Conclusions: Post‐LT patients are at increased risk of CVS morbidity even in the absence of pre‐existing metabolic risk factors. Renal sparing immunosuppressive protocols might reduce CVS events post‐LT.